Deficiency in the Phosphorylated Pathway of Serine Biosynthesis Perturbs Sulfur Assimilation. Issue 1 (20th February 2019) - Anoman, Armand D.; Flores-Tornero, María; Benstein, Ruben M.; Blau, Samira; Rosa-Téllez, Sara; Bräutigam, Andrea; Fernie, Alisdair R.; Muñoz-Bertomeu, Jesús; Schilasky, Sören; Meyer, Andreas J.; Kopriva, Stanislav; Segura, Juan; et al.
Abstract : The Phosphorylated Pathway of l -Ser Biosynthesis in Arabidopsis thaliana provides Ser for thiol assimilation in heterotrophic tissues such as roots. Abstract: Although the plant Phosphorylated Pathway of l -Ser Biosynthesis (PPSB) is essential for embryo and pollen development, and for root growth, its metabolic implications have not been fully investigated. A transcriptomics analysis of Arabidopsis ( Arabidopsis thaliana ) PPSB-deficient mutants at night, when PPSB activity is thought to be more important, suggested interaction with the sulfate assimilation process. Because sulfate assimilation occurs mainly in the light, we also investigated it in PPSB-deficient lines in the day. Key genes in the sulfate starvation response, such as the adenosine 5′phosphosulfate reductase genes, along with sulfate transporters, especially those involved in sulfate translocation in the plant, were induced in the PPSB-deficient lines. However, sulfate content was not reduced in these lines as compared with wild-type plants; besides the glutathione (GSH) steady-state levels in roots of PPSB-deficient lines were even higher than in wild type. This suggested that PPSB deficiency perturbs the sulfate assimilation process between tissues/organs. Alteration of thiol distribution in leaves from different developmental stages, and between aerial parts and roots in plants with reduced PPSB activity, provided evidence supporting this idea. Diminished PPSB activity caused an enhanced flux of 35 S into thiol biosynthesis, especially in roots. GSH turnover also accelerated in the PPSB-deficient lines, supporting the notion that not only biosynthesis, but also transport and allocation, of thiols were perturbed in the PPSB mutants. Our results suggest that PPSB is required for sulfide assimilation in specific heterotrophic tissues and that a lack of PPSB activity perturbs sulfur homeostasis between photosynthetic and nonphotosynthetic tissues.